Olea neriifolia H. L. Li, a new record species of the family Oleaceae for the flora of Vietnam - Quang, Bui Hong; Cuong, Nguyen The (Academia Journal of Biology, 2015)
The genus Olea L. (Olive) comprises about 40 species worldwide, distributed in Afica, Asia, Europe, Australia and Pacific Islands. In Vietnam, up to date there were 9 species belonging to the genus Olea recorded. Based on the samples of Olea kept in the herbarium, as well as domestic and foreign publications, we found one species, Olea neriifolia H. L. Li, as a new record for the flora of Vietnam. Voucher specimens of this species were collected in Quang Ninh province (Ha Long bay) and Khanh Hoa (Cam Lam), deposited in the Herbarium of the Institute of Ecology and Biological resources, Hanoi, Vietnam (HN). The newly recorded species has the morphological differences from the already known species of Vietnam, thus the total number of species of this genus is ten. In this paper some detailed morphological features of Olea neriifolia is given. A key to species of the genus Olea in Vietnam is also provided.